2018
DOI: 10.1038/s41598-018-23699-3
|View full text |Cite
|
Sign up to set email alerts
|

Altered connection properties of important network hubs may be neural risk factors for individuals with primary insomnia

Abstract: Primary insomnia (PIs) is highly prevalent and can lead to adverse socioeconomic impacts, but the underlying mechanism of its complex brain network impairment remains largely unknown. Functional studies are too few and diverse in methodology, which makes it difficult to glean general conclusions. To answer this question, we first used graph theory-based network analyse, together with seed-based functional connectivity approach, to characterize the topology architecture of whole-brain functional networks associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 79 publications
4
52
0
Order By: Relevance
“…Its magnitude remained strong, even after we controlled for relevant covariates (i.e., age, sex, TIV) and type I errors. Interestingly, we also found that these identified global regions are components of large-scale brain networks categorized by a large body of functional magnetic resonance imaging (fMRI) studies with adult study populations in clinical settings and nonclinical settings 32,[35][36][37][38][39][40][41][42][43] . The networks include the default mode network (DMN), central executive network (CEN), visual network (VN), somatosensory network (SSN), and salience network (SN).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Its magnitude remained strong, even after we controlled for relevant covariates (i.e., age, sex, TIV) and type I errors. Interestingly, we also found that these identified global regions are components of large-scale brain networks categorized by a large body of functional magnetic resonance imaging (fMRI) studies with adult study populations in clinical settings and nonclinical settings 32,[35][36][37][38][39][40][41][42][43] . The networks include the default mode network (DMN), central executive network (CEN), visual network (VN), somatosensory network (SSN), and salience network (SN).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a smaller GMV in the right middle superior frontal gyrus has also been shown to be correlated with a later bedtime on weekends in 14-year-old community adolescents 23 . The DMN is conventionally regarded as a network that is active when the brain is at rest, yet there is compelling evidence that the DMN also plays an important role in sleep as well as in other activities 37,52 . A growing body of structural and functional neuroimaging studies have demonstrated that altered GMVs and functional connectivity within the DMN are linked not only to sleep problems, but also to other symptoms of sleep problems, including poor cognitive functions 30,45,53 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the underlying mechanism of taVNS in alleviating PI is not fully clarified. A recent fMRI study illustrated that PI was associated with altered connection properties of intra-networks within the executive control network, default mode network (DMN) and salience network (Liu et al, 2018). Our previous studies showed that taVNS can alleviate insomnia in depression patients by regulating the function of DMN in depression (Fang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%